2021
DOI: 10.1097/md.0000000000026849
|View full text |Cite
|
Sign up to set email alerts
|

Effect of molecular targeted agents in chemotherapy for treating platinum-resistant recurrent ovarian cancer

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…A meta-analysis has demonstrated that combination therapy with VEGF/VEGFR inhibitors yields superior survival benefits compared to chemotherapy for patients with PROC [ 42 ]. However, the trials included in the analysis encompassed recurrent OC rather than exclusively focusing on platinum-resistant disease, and they encompassed a subset of patients with platinum-sensitive disease as well.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis has demonstrated that combination therapy with VEGF/VEGFR inhibitors yields superior survival benefits compared to chemotherapy for patients with PROC [ 42 ]. However, the trials included in the analysis encompassed recurrent OC rather than exclusively focusing on platinum-resistant disease, and they encompassed a subset of patients with platinum-sensitive disease as well.…”
Section: Discussionmentioning
confidence: 99%
“…Additional courses of platinum-based chemotherapy are of little benefit for these platinum-resistant patients and most of these patients soon die of disease. A smaller group of patients who relapse may be platinum-sensitive and will respond favorably to additional regimens of platinum-based chemotherapy and enjoy much longer survival [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last three decades, there has been little improvement in the survival of patients with ovarian cancer [ 3 , 7 ]. This underscores the urgency of providing adequate management strategies and novel treatments for those afflicted with this disease [ 4 , 8 ]. In this effort, novel therapies, such as immune checkpoint inhibitors including anti-programmed death-1 (anti-PD-1) antibodies, have been investigated in ovarian cancer clinical trials, but these immunotherapy agents only give marginal improvements to patient outcome [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%